The Effect of Parental Deprivation on Consciences Awakening, underprivileged and non-deprived Among Adolescents - Al-Tarawneh, Ishraq Yousef (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the effect of deprivation from the father or mother or both on consciences awakening, among adolescents. the sample of the study consisted of the whole 198 male and female deprived adolescents in Al-Karak province who attain school there and reside in social care centers, in addition to 200 non-deprived male and female adolescents. The study relied on the descriptive analytical correlational approach To achieve the goals of the study, were constructed: consciences awakening scale. After checking for reliability and validity of these tools, they were applied on the sample of the study. The results indicated that means of non-deprived adolescents were higher on consciences awakening, than deprived adolescents. Results also indicated significant statistical differences that are attributed to the effect of gender on consciences awakening and these differences were in favor of females, while there were no significant statistical differences that are attributed to type of deprivation, and the interaction between gender and type of deprivation. Results also indicated significant statistical differences among deprived of father male participants and deprived of mother female participants on consciences awakening, and these differences were in favor of deprived of mother females. in addition, there were also significant statistical differences on place of residence on consciences awakening in favor of those adolescents who reside with their families. There were no significant statistical differences for the interaction between gender and place of residence. Finally the study concluded with the recommendation of offering social support for deprived students through activating school counseling.